PELATIHAN PEMBUATAN NUGGET DAN STIK RUMPUT LAUT GUNA MENDUKUNG PENGEMBANGAN PRODUK PANGAN LOKAL MASYARAKAT DESA HUILELOT KECAMATAN SEMAU - Immaria Fransira; Asriati Djonu; Yudiana Jasmanindar; Wesly Pasaribu; Theny Intan Berlian Kurniati Pah (Universitas Mataram, 2025)
Huilelot Village is famous as one of the centers of seaweed cultivation in Kupang Regency. The low level of seaweed processing is one of the problems faced by the community of Huilelot Village. Until now, the villagers have only produced wet and dry seaweed, and its processing is limited to personal consumption. Therefore, the process is still not optimal. Therefore, the purpose of this training activity is to increase the knowledge and skills of the people of Huilelot Village, Semau District, regarding the diversification of cultivated seaweed products to overcome the problems faced by the community and also to improve their welfare. The methods used in this community service activity consist of the preparation stage, the implementation stage, and the monitoring stage. The participants of this activity were members of the PKK from four hamlets. This activity demonstrated the community's increased knowledge and skills in processing seaweed nuggets and sticks, as well as their marketing. The increase in knowledge was demonstrated based on the results of the pre-test and post-test evaluations. In addition, these PKK members have also produced their own seaweed nuggets and sticks. The production of seaweed nuggets and sticks is a solution to overcome the problems faced by partners. It is hoped that this will become a local food product in the future in Huilelot Village.